Genetic and Non-genetic Factors Contributing to the Significant Variation in the Plasma Trough Concentration-to-Dose Ratio of Valproic Acid in Children With Epilepsy - Xu, Ze-Yue; Guo, Hong-Li; Li, Ling; Zhang, Min; Jing, Xia; Xu, Ze-Jun; Qiu, Jin-Chun; Lu, Xiao-Peng; Ding, Xuan-Sheng; Chen, Feng; Xu, Jing (Frontiers in Pediatrics, 2021)
Objective: To evaluate potential genetic and non-genetic factors contributing to plasma trough concentration-to-dose (C0/D) ratio of valproic acid (VPA) in pediatric patients with epilepsy. Study design: A single-center, retrospective cohort study was performed by collecting data from 194 children aged 1 to 14 years between May 2018 and November 2018. The oral solution (n=135) group and sustained-release (SR) tablet group (n=59) were defined, and the plasma VPA C0 was measured. Twenty-six single-nucleotide polymorphisms (SNPs) were chosen for genotyping with the MassARRAY system. A multiple logistic regression model was used for data analysis. Results: Body weight (BW) and age were positively correlated with the C0/D ratio in 194 patients, but the positive correlation disappeared after the patients were divided into oral solution and SR tablet subgroups. The average C0/D ratio was significantly increased by 2.11-fold (P = 0.000) in children who took VPA SR tablets compared with children who were administered VPA oral solutions. No significant association between genetic variants and the C0/D ratio was found, even for the five well-studied SNPs including UGT2B7 G211T, C802T, C161T, T125C, and CYP2C9*3 A1075C. However, a significant association between the C0/D ratio and UGT1A6/9 Del＞A (rs144486213) was observed in the VPA oral solution group, but not in the VPA SR tablet group. Conclusions: The dosage forms of sodium valproate, rather than BW, age, or genetic polymorphisms, significantly affected the VPA C0/D ratios in pediatric patients with epilepsy. Based on our findings, switching the dosage form between solution and SR tablet should be performed cautiously. Total daily dose adjustment should be considered, and the plasma concentration, seizure-control effect, and adverse drug reaction should also be monitored very closely.